Home Industry Kekinian Ibu Rumah Tangga Hunian Barak Melalui Pelatihan Teknik Jahit Quilting Kain Perca di Kota Kuala Kapuas - Tiawon, Harin; Harysakti, Ave; Heriamariaty, Heriamariaty; Amiany, Amiany (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
Selat Barat Subdistrict is a densely populated residential area where people live in tenement barracks. In these Barracks residensials there are many housewives of productive age between 30-46 years mostly had junior high school (SMP) education and have a lot of free time. One of them is the RT.008/ RW.004 Barracks, Selat Barat Village. The existence of Modern Home Industry for housewives can be a solution to improve the region's economy. The potential Contemporary Home Industry as a creative craft product can be a solution in increasing the level of income and welfare of the people in Selat Barat Subdistrict by producing products with minimal cost and higher selling price in the Kuala Kapuas City area. Apart from that, there has never been such contemporary craft in the Central Kalimantan Province region in particular. Therefore, it is necessary to provide training in patchwork quilting sewing techniques. This training includes: (1) preparation, namely preparing training modules, basic knowledge of trial patchwork quilting sewing techniques; (2) implementation of training: making patterns, printing patterns onto fabric, cutting and joining, sewing or connecting; (3) evaluation. The results of the training to make contemporary home industry products for housewives include negligees, tops, dresses and shorts from patchwork Keywords : Home Industry, Contemporary, Quilting, Patchwork